Endoscopic management of a delayed diagnosed foreign body esophageal perforation - Rodrigues-Pinto,Eduardo (2014)
Foreign body-induced perforation is responsible for 16.7% of esophageal perforations and may be associated with respiratory failure, sepsis or hemorrhage if delayed diagnosis and treatment. The mortality rate of esophageal perforations hovers close to 20%, especially if treatment is delayed more than 24 h. Esophageal perforation management remains controversial and treatment decisions should be individualized depending on the etiology of perforation, degree of mediastinopleural contamination, underlying esophageal disease, and overall health status of the patient. We report a case of successful endoscopic management in a delayed diagnosis of an esophageal perforation presenting with an associated peri-esophageal abscess.